Case Report: Unveiling the unexpected: a rare case of adult-type rhabdomyoma in a 9-year-old boy - Wang, Li; Li, Shan; Sun, Lingling (Frontiers in Pediatrics, 2025)
Rhabdomyoma is an exceedingly rare benign soft tissue tumor of skeletal muscle origin, classified into cardiac and extracardiac types based on location. Extracardiac rhabdomyoma further includes adult, genital, and fetal types depending on the degree of differentiation. Most patients are between 40 and 70 years old, with a mean age of 60 years and a male predominance. This case report presents a 9-year-old boy diagnosed with an oropharyngeal tumor, initially presenting with a 6-month history of a foreign body sensation in the throat, presenting as night-time snoring. Postoperative histological examination revealed adult rhabdomyoma, characterized by specific immunohistochemical and histologic traits including cytoplasmic positivity for muscle-specific Actin (MSA), Desmin, Myogenin, and MYOD1, large polygonal skeletal muscle cells and frequent extensive vacuolization. This report highlights the unusual age of presentation for this variant and underscores the need for heightened clinical awareness to ensure accurate diagnosis and effective management of such rare occurrences.